Measuring Bond Price Volatility - Livingston, Miles (Journal of Financial and Quantitative Analysis, 1979)
In the literature dealing with bond price volatility, there have been two divergent approaches. On the one hand, theoretical papers have looked at bond price volatility in the instantaneous framework of the calculus. Using the derivative of bond price (P) with respect to yield to maturity (y), it has been shown that volatility is linearly related to this derivative (dP/dy). (See [10].)